UGT1A1 polymorphisms in cancer: impact on irinotecan treatment - Takano M; Sugiyama T (Dove Medical Press, 2017)
Masashi Takano1 Toru Sugiyama2 1Department of Clinical Oncology, National Defense Medical College Hospital, Tokorozawa, Saitama, 2Department of Obstetrics and Gynecology, Iwate Medical University, Morioka, Iwate, Japan Abstract: Mutations in the UGT1A1 gene have been implicated in Gilbert syndrome, which shows mild hyperbilirubinemia, and a more aggressive childhood subtype, Crigler–Najjar syndrome. To date, more than 100 variants have been found in the UGT1A1 gene. Among them, UGT1A1*28 and UGT1A1*6 have been reported to be associated with severe toxicities in patients treated with irinotecan-based chemotherapy by increasing the dose of SN-38 (7-ethyl-10-hydroxycamptothecin), an active form of irinotecan. Many association studies and meta-analyses have demonstrated the contribution of UGT1A1*28 and UGT1A1*6 polymorphisms to the toxicities caused by irinotecan-based therapy. The aim of this review was to evaluate the impact of these variants upon the toxicities and the efficacy of irinotecan-based chemotherapy. Keywords: UGT1A1, irinotecan, chemotherapy, toxicity, response, survival